2003
DOI: 10.1002/chin.200333168
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Trianglimines: Scope and Limitations of the [3 + 3] Cyclocondensation Reaction Between (1R,2R)-Diaminocyclohexane and Aromatic Dicarboxaldehydes.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…[9,10] We have shown that trianglimines can be obtained from almost any synthetically accessible aromatic dialdehyde with complete control of the size of the macrocycle and functionalities incorporated into the aromatic moiety. [10][11][12][13][14] More importantly, we have demonstrated that trianglimines can be incorporated into more sophisticated structures such as catenanes and shown their promise in chiral recognition. [15,16] Trianglimines are characterized by their structural diversity, ease of synthesis in quantitative yields and most importantly by their chirality, where both enantiomers of any derivative are readily available in a pure form.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…[9,10] We have shown that trianglimines can be obtained from almost any synthetically accessible aromatic dialdehyde with complete control of the size of the macrocycle and functionalities incorporated into the aromatic moiety. [10][11][12][13][14] More importantly, we have demonstrated that trianglimines can be incorporated into more sophisticated structures such as catenanes and shown their promise in chiral recognition. [15,16] Trianglimines are characterized by their structural diversity, ease of synthesis in quantitative yields and most importantly by their chirality, where both enantiomers of any derivative are readily available in a pure form.…”
mentioning
confidence: 91%
“…Trianglamines are readily synthesized in quantitative yields by reducing trianglimines with sodium borohydride . We have shown that trianglimines can be obtained from almost any synthetically accessible aromatic dialdehyde with complete control of the size of the macrocycle and functionalities incorporated into the aromatic moiety . More importantly, we have demonstrated that trianglimines can be incorporated into more sophisticated structures such as catenanes and shown their promise in chiral recognition .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of DCL building blocks we have chosen aromatic dialdehydes in combination with dihydrazides based on tartaric acid. We have shown that dialdehydes in combination with diamines are able to form trianglimine macrocycles allowing large variability in the dialdehyde building block . Recently, we have shown that using real‐time mass spectrometry (MS), we could detect all intermediates in a DCL formation along with probing the dynamic reversibility of the process .…”
mentioning
confidence: 99%